Modeling potato virus Y disease dynamics in a mixed-cropping system. (4th May 2022) - Degefa, D.S.; Makinde, O. D.; Temesgen, D.T.
ABSTRACT: Potato virus Y (PVY) is a serious pathogen that causes yield reduction and seed degeneration in potatoes crops. It is transmitted non-persistently by a wide range of aphid vectors. The transmission process is rapid and can be affected by vector behavior exhibited during host search and feeding. Controlling aphids by insecticide is inefficient to manage PVY while, mixed-cropping system comprises potatoes and non-host crop plants is an important strategy. Studies about the significance of such practices will benefit smallholder farmers. We formulate a mathematical model that aims to investigate effects of mixed-cropping system on the PVY disease dynamics. Analysis results show that the non-virus host plant is important to reduce the basic reproduction number, ℜ 0 of the disease. If ℜ 0 < 1, then the disease-free equilibrium is globally stable; if ℜ 0 > 1, then an endemic equilibrium exists which is locally asymptotically stable. We employed a geometric approach and discuss conditions for global stability of the endemic equilibrium. Bifurcation and sensitivity analysis of the embedded parameters were also carried out. Finally, some numerical simulations are conducted to support analytic results.